2022
DOI: 10.1002/cpt.2611
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Extended Oral Anticoagulant Therapy in Patients with Venous Thromboembolism: A Retrospective Cohort Study

Abstract: Limited real‐world evidence exists for effectiveness and safety of extended oral anticoagulation beyond 6 months of initial treatment in prevention of recurrent venous thromboembolism (VTE) and adverse major bleeding events among patients with VTE. Using MarketScan Commercial and Medicare Supplemental databases (2013–2019), we conducted a retrospective cohort study to compare the risk of recurrent VTE and major bleeding events during extended treatment among patients with VTE who completed the 6‐month initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
3
1
Order By: Relevance
“…Whereas the AMPLIFY‐EXT trial showed reduced recurrent VTE risk without increasing the major bleeding risk with extended apixaban therapy compared with placebo during 12 months' follow‐up after 6–12 months of initial treatment, the present study extends these findings by comparing apixaban to another commonly used anticoagulant, warfarin. In a recent study by a member of our team comparing extended apixaban therapy versus extended warfarin therapy in commercially insured patients, use of apixaban was associated with a decreased risk of a major bleed, but no differences in recurrent VTE risk was observed, whereas the present study found that extended‐apixaban use was associated with reduced recurrent VTE risk without an increased risk of a major bleed 31 . We also showed that mortality was higher among individuals with provoked versus unprovoked VTE, with versus without cancer, and with versus without chronic kidney disease for extended apixaban therapy compared with warfarin or with no extended therapy, an observation that may be partially explained by the older adults included in our study (mean age of 72–73 years vs. 58 years in AMPLIFY‐EXT) 32,33 .…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Whereas the AMPLIFY‐EXT trial showed reduced recurrent VTE risk without increasing the major bleeding risk with extended apixaban therapy compared with placebo during 12 months' follow‐up after 6–12 months of initial treatment, the present study extends these findings by comparing apixaban to another commonly used anticoagulant, warfarin. In a recent study by a member of our team comparing extended apixaban therapy versus extended warfarin therapy in commercially insured patients, use of apixaban was associated with a decreased risk of a major bleed, but no differences in recurrent VTE risk was observed, whereas the present study found that extended‐apixaban use was associated with reduced recurrent VTE risk without an increased risk of a major bleed 31 . We also showed that mortality was higher among individuals with provoked versus unprovoked VTE, with versus without cancer, and with versus without chronic kidney disease for extended apixaban therapy compared with warfarin or with no extended therapy, an observation that may be partially explained by the older adults included in our study (mean age of 72–73 years vs. 58 years in AMPLIFY‐EXT) 32,33 .…”
Section: Discussioncontrasting
confidence: 68%
“…In a recent study by a member of our team comparing extended apixaban therapy versus extended warfarin therapy in commercially insured patients, use of apixaban was associated with a decreased risk of a major bleed, but no differences in recurrent VTE risk was observed, whereas the present study found that extended‐apixaban use was associated with reduced recurrent VTE risk without an increased risk of a major bleed. 31 We also showed that mortality was higher among individuals with provoked versus unprovoked VTE, with versus without cancer, and with versus without chronic kidney disease for extended apixaban therapy compared with warfarin or with no extended therapy, an observation that may be partially explained by the older adults included in our study (mean age of 72–73 years vs. 58 years in AMPLIFY‐EXT). 32 , 33 In addition, a sensitivity analysis in which we conducted ITT analyses and an analysis with extended exposure effect windows from 7 days to 60 days after patients discontinued therapy provided results that were generally consistent with these findings.…”
Section: Discussionsupporting
confidence: 52%
“…Although a direct comparison of our results with those from previous studies was not feasible because of a lack of established literature on the risk of second recurrent VTE, our findings were largely consistent with those showing clinical benefits of DOAC use compared with warfarin use for preventing recurrent VTE without increasing the risk of major bleeding events during extended treatment. 21,22 Furthermore, there was no difference in subgroup analyses by active cancer, CKD, bleeding risk score, or type Our study has several limitations. First, although we used IPTW to balance differences in patient characteristics between the two groups, we could not rule out unmeasured confounders, such as international normalized ratio, genetic factors associated with patientspecific warfarin dose (e.g., VKORC1, CYP2C9, and CYP4F2 variants), or race and ethnicity that might be related to the outcome occurrence.…”
Section: Discussionmentioning
confidence: 78%
“…Although a direct comparison of our results with those from previous studies was not feasible because of a lack of established literature on the risk of second recurrent VTE, our findings were largely consistent with those showing clinical benefits of DOAC use compared with warfarin use for preventing recurrent VTE without increasing the risk of major bleeding events during extended treatment. 21 , 22 Furthermore, there was no difference in subgroup analyses by active cancer, CKD, bleeding risk score, or type of first recurrent VTE, suggesting that DOAC therapy is a reasonable option for treatment after recurrent VTE in various populations.…”
Section: Discussionmentioning
confidence: 96%
“…One recent retrospective cohort study found that extended treatment with apixaban or warfarin (>6 months) was associated with reduced risk of recurrent VTE compared with no extended treatment among commercially insured patients; however, extended treatment with warfarin was also associated with increased risk of major bleeding. 8 There remains a paucity of evidence describing adherence to DOAC or warfarin extended-phase therapy or their effects on the risks of recurrent VTE and major bleeding among patients with VTE. Thus, we aimed to identify trajectories of adherence to extended-phase treatment with DOACs or warfarin using group-based trajectory models (GBTM) and to assess the association of these adherence trajectories with risks of recurrent VTE and major bleeding among individuals with VTE after 6 months' initial anticoagulant therapy.…”
Section: Introductionmentioning
confidence: 99%